Foods, the Best Way to Take Antioxidant Natural Products - Maria Eduarda Machado Araújo; Alice Martins (Foods, 2020)
Antioxidants are powerful compounds that help the body to destroy the excess of endogenous radical species responsible for many severe conditions like neurodegenerative, inflammatory, and cardiovascular impairments, and even some forms of cancer [...]